Pengaruh Implementasi Sistem Manajemen Mutu ISO 9001:2015 terhadap Mutu Layanan Akademik di Sekolah Menengah Kejuruan Negeri 3 Bandung - Fauzi Nugraha Kurnia, ( - ) (2020)
This research was conducted at SMK Negeri 3 Bandung. This study aims to determine the effect of the implementation of the ISO 9001: 2015 quality management system on the quality of academic services at SMK Negeri 3 Bandung. This research uses descriptive research and verification method of explanatory survey with data collection techniques using a questionnaire. The population in this study were 2154 respondents and the sample in this study was 436 respondents. And the data analysis technique used is simple linear regression. The results of data processing show that the implementation of the ISO 9001: 2015 quality management system is in the almost effective category, the description of the quality of academic services is in the high category. The results of the hypothesis test show that the implementation of the ISO 9001: 2015 (X) Quality Management System has a significant and positive effect on the quality of academic services (Y).